Perbaikan kualitas lindi TPA Batu Layang menggunakan arang batok kelapa, arang kulit durian dan pasir - Irwan Lovadi, Ika Nurmaja, Tri Rima Setyawati, (Jurnal Protobiont, 2014)
The alternative filter mediaÂ  that Â used to process the leachate water is charcoal and sand. This research aims to determine the effectiveness of using coconut shell charcoal, durian rind charcoal and sand in improving the quality of leachate in terms of the Total Suspended Solid (TSS), Total Disolve Solid (TDS), pH, Chemical Oxygen Demand (COD) parameters and the number of bactery colonies. This research was conducted for three months from December 2013 to February 2014. The research was designed by using the Randomized Block Design (RBD) with each coconut shell charcoal and sand has 10 cm thickness (treatment K), each durian rind charcoal and sand has 10 cm thickness (treatment D), each coconut shell charcoal, durian rind charcoal, and sand has 10 cm thickness (treatment KD), and sand has 10 cm thickness (control). The value of TSS, TDS, pH, COD and the number of bactery colonies before treatment were 430 mg/L, 1142 mg/L, 5.73, 92.27 mg/L and 407.7 x 105 CFU/ml. The most effective treatment was each coconut shell charcoal, durian rind charcoal and sand has 10 cm thickness which can reduce TSS 46.91%, TDS 47.00%, COD 47.03%, and the number of bacteria colonies 40.96% and increased the pH 7.33.